2008
DOI: 10.1111/j.1365-2656.2008.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual specialization in diet by a generalist marine predator reflects specialization in foraging behaviour

Abstract: Summary 1.We studied chick diet in a known-age, sexed population of a long-lived seabird, the Brünnich's guillemot ( Uria lomvia ), over 15 years ( N = 136; 1993-2007) and attached time-depth-temperature recorders to examine foraging behaviour in multiple years ( N = 36; 2004-07). 2. Adults showed specialization in prey fed to offspring, described by multiple indices calculated over 15 years: 27% of diet diversity was attributable to among-individual variation (withinindividual component of total niche width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
259
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(283 citation statements)
references
References 107 publications
15
259
2
Order By: Relevance
“…It was impossible to improve this quantification due to large differences in the degree of digestion of the samples and the uncertainty as to how many meals each regurgitation represented. To avoid possible pseudoreplication through possible diet specialization by individual birds (Woo et al 2008), only one diet sample (stomach and/or chick) was collected from an adult. Means are given ±1 standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…It was impossible to improve this quantification due to large differences in the degree of digestion of the samples and the uncertainty as to how many meals each regurgitation represented. To avoid possible pseudoreplication through possible diet specialization by individual birds (Woo et al 2008), only one diet sample (stomach and/or chick) was collected from an adult. Means are given ±1 standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…[13 -15]), results are not conclusive, suggesting under some conditions, generalists are favoured [15,16]. Theoretical predictions infer that if groups experience different levels of environmental heterogeneity, the selective pressures favouring specialization may also vary [17], offering some explanation for differences between populations.…”
Section: Introductionmentioning
confidence: 99%
“…Woo et al (2008), pointed out that over long periods, with fluctuating prey levels, different foraging strategies may balance out. Recent studies (van de Pol et al 2009(van de Pol et al , 2010 showed also the necessity to consider appropriate time-scale to understand the mechanism by which environmental change affects the evolution and maintenance of diet specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary differences among individuals may be also related to differences in foraging. For example, Woo et al (2008) showed that individual diet specialization in a Brünnich's guillemot (Uria lomvia) population was related to foraging behaviour as guillemots specialize on a single foraging strategy across years, regarding flight time, dive depth and dive shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation